2011
DOI: 10.4162/nrp.2011.5.3.236
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between attention deficit hyperactivity disorder and sugar consumption, quality of diet, and dietary behavior in school children

Abstract: This study investigated the correlation between consumption of sugar intake by fifth grade students in primary schools and development of Attention Deficit Hyperactivity Disorder (ADHD). A total of 107 students participated, and eight boys and one girl (8.4% of the total) categorized as high risk for ADHD according to diagnostic criteria. There were significant differences in the occupations and drinking habits of the respondents' fathers between the normal group and risk group. In a comparison of students' nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 11 publications
2
38
0
2
Order By: Relevance
“…Sweet foods are relevant to sucrose that could produce a rapid rise of blood glucose, which in turn induces a rapid fall to a level that disrupts brain function (11,34) . Less sugar from fruit snacks and/or lower vitamin C intake has been reported to have a positive association with the risk for attention-deficit hyperactivity disorder in school-aged Korean children (35) , although the adverse influence of sugar is not clear (34) . Glucose may need a shorter period of time to respond to human body needs than micronutrients (34) .…”
Section: Discussionmentioning
confidence: 99%
“…Sweet foods are relevant to sucrose that could produce a rapid rise of blood glucose, which in turn induces a rapid fall to a level that disrupts brain function (11,34) . Less sugar from fruit snacks and/or lower vitamin C intake has been reported to have a positive association with the risk for attention-deficit hyperactivity disorder in school-aged Korean children (35) , although the adverse influence of sugar is not clear (34) . Glucose may need a shorter period of time to respond to human body needs than micronutrients (34) .…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that have suggested that children with ADHD have lower levels of zinc and copper, 22 as well as a decreased intake of Vitamin C. 23 It is possible that dietary intake in children with ADHD may be an unidentified confounder for constipation and fecal incontinence.…”
Section: Figurementioning
confidence: 99%
“…Balanced nutrition is important during childhood and adolescence, which are periods of growth, development of body functions, and social cognitive ability (3). Behavioral and social skills achieved in childhood may determine the person's ability to cope with the many demands of modern society (4).…”
mentioning
confidence: 99%